(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Ever since the publication of the UN Universal Declaration of Human Rights, the notion of human dignity has been regarded as the moral foundation on which human rights and liberties function. This article argues that unless dignity is grounded in a theological understanding of human nature and human worth, as portrayed in the creation accounts of Genesis 1-2, dignity is too ambiguous a notion to be useful in contemporary debates. It is argued that the creation of humankind in God’s image and the special task of administering the creation humans receive from the Creator, speak both about the value human beings have and therefore about their dignity.